The Relationship Between Perceptions of Service Value and Service Quality on Customer Satisfaction - Jalaludin Al-Mahali (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This research aims to determine the relationship value perception service and quality of service to customer satisfaction. The type of research used in this study is quantitative with the sample is the Guardian student of SMK 57 Jakarta as many as 130 guardians of students. Sampling method using Simple Random Sampling, each guardian of students has the same opportunity to be sampled and method of collecting data in the form of poll or questionnaire. Based on output results using SPSS statistical tools version 23 known that: (1) Service Value Perception Affects Customer Satisfaction; (2) Quality of service affects customer satisfaction; (3) The perception of service value and quality of service affects customer satisfaction.Â